Perceptions of libraries and information resources a report to the OCLC membership - De Rosa, Cathy (OCLC Online Computer Library Center, 2005)
This report to the OCLC membership summarizes findings of an international study on information-seeking habits and preferences. It provides the findings and responses from an online survey in an effort to learn more about library use, awareness and use of library electronic resources, the Internet search engine, the library and the librarian, free vs. for-fee information, and the "library" brand.